Development of the Tourism Industry as the Motor of Economic Growth in Indonesia - Dyah Poespita Ernawati (GoAcademica Research & Publishing, 2019)
The tourism sector is one of the activities that have a strategic role in supporting international economic development in the era of globalization influencing the development of the tourism industry for the development of areas around tourist objects so that they can act as a leading industry, sectors that can improve the economy. The existence of the tourism sector will create jobs that will increase the income of people in tourist areas. When linked to economic development with balanced growth, tourism can be expected to play a decisive role and be a catalyst for developing its development sector. Meanwhile, the economic impact of tourism development can be positive or negative. The positive effects are (1) creating jobs, (2) increasing opportunities, (3) increasing community income in the surrounding tourist areas. Meanwhile, the environment's negative impact is the natural environment, the built environment, and culture.